Effect of a Surfactant on the Electric-Field Assembly of Oil-Water Emulsions for Making Foam Targets. (1st September 2016) - Chock, B. P.; Jones, T. B.; Harding, D. R.
Abstract: The electric-field–assembly technique proposed for making fusion targets uses the electrical force from dielectrophoresis and electrowetting-on-dielectric phenomena to form droplets of oil and water, combine them into an emulsion, and then center one phase inside the surrounding immiscible phase. Forming the water droplet becomes more problematic with the addition of a surfactant, which is needed to stabilize an oil-in-water emulsion. The effect of increasing the amount of surfactant on the droplet-dispensing process is presented, and a mechanism for this behavior is provided. Increasing the surfactant concentration slows the rate at which surfactant-water droplets are dispensed and increases the variability in the volume of successive droplets. This effect becomes more pronounced near the critical micelle concentration (CMC). Increasing the applied electric field (V > 75 Vrms ) improves the dispensing process but decreases the lifetime of the dielectric coatings (for V > 125 Vrms ). The stronger electric field forces surfactant molecules to aggregate at the edges of the water droplet where the electrical forces are the greatest. The difficulty of separating a surfactant-laden droplet from the bulk fluid is attributed to the reduced liquid-air surface tension, the lower liquid-substrate surface energy, and a higher disjoining pressure in the thin-film membrane attaching the droplet to the bulk fluid. The parameters studied include the surfactant concentration (Silwet L-77) from 0 to 0.025 wt% (2.5 × the CMC limit), the voltage from 75 to 150 Vrms, and the frequency from 0.1 to 10 kHz.